TSPAN4+ fibroblasts coordinate metastatic niche assembly through migrasome-driven metabolic reprogramming and stromal-immune crosstalk in pancreatic adenocarcinoma - Hu, Qingwen; Chen, Jiali; Liu, Yang; Chen, Haiqing; Lai, Haotian; Jiang, Lai; Zhou, Xuancheng; Zhang, Shengke; Huang, Jinbang; Chi, Hao; Li, Bo; Zhong, Xiaolin (Frontiers in Immunology, 2025)
BackgroundPancreatic cancer (PC) is a highly aggressive pancreatic malignant tumor with poor prognosis due to its complex tumor microenvironment (TME) and metastatic potential. Fibroblasts play an important role in tumor progression and metastasis by remodeling the extracellular matrix (ECM) and influencing the immune response. This study explored migrasome-associated fibroblasts, especially TSPAN4 and ITGA5, as key regulators of pancreatic cancer metastasis, aiming to provide new ideas for therapeutic strategies targeting TME.MethodsWe employed single-cell RNA sequencing (scRNA-seq) and spatial transcriptomics to analyze pancreatic cancer tissues. Data from the GEO and TCGA databases were integrated and processed using batch correction techniques. Single-cell data were analyzed with Seurat and Monocle for dimensionality reduction and pseudotime trajectory analysis. Cell communication was assessed using CellCall and CellChat. Spatial transcriptomic analysis was conducted with RCTD and MISTy tools to investigate cell interactions within the TME. Additionally, gene enrichment, deconvolution, and prognostic analyses were performed, alongside experimental validation through siRNA transfection, qRT-PCR, and various functional assays to investigate the role of TSPAN4 in metastasis.ResultsOur results underscore the critical role of TSPAN4+ fibroblasts in pancreatic cancer. These fibroblasts were predominantly located at the tumor periphery and exhibited elevated migrasome gene expression, which was associated with enhanced ECM remodeling and immune suppression. Intercellular communication analysis revealed that TSPAN4+ fibroblasts engaged in extensive interactions with immune cells, such as macrophages and endothelial cells, facilitating metastasis and immune evasion. Moreover, the high expression of immune checkpoint markers indicated their involvement in modulating the immune response.ConclusionTSPAN4+ fibroblasts are key regulators of pancreatic cancer progression, contributing to metastasis, immune suppression, and ECM remodeling. Targeting these fibroblasts represents a promising therapeutic strategy to improve clinical outcomes and enhance the effectiveness of immunotherapies in pancreatic cancer.